Perbandingan Keamanan dan Performa Aplikasi WhatsApp dan Telegram dengan Menggunakan Metode NIJ - Aulyahzakilah Ifani; Andi Mawaddah Sumardi; Novera Baytikhalishah; Nurlela (Journal of Cyber Health and Computer, 2023)
In the current era of information technology, humans have experienced convenience and efficiency in their lives, thanks to social media. Various types of social media platforms have emerged, including social networking platforms such as Facebook and LinkedIn, photo and video sharing platforms like Instagram and TikTok, and instant messaging platforms like WhatsApp and Telegram. In this research, we conducted experiments to compare the performance of WhatsApp and Telegram applications using various tools such as Virtex, FTK Imager, Autopsy, and Metasploit, on Windows 11, Android 8 and 11 operating systems, as well as Kali Linux, using the NIJ method. Based on the analysis conducted, all experiments were unsuccessful. The latest versions of WhatsApp and Telegram were found to be secure against Virtex attacks, FTK Imager was ineffective in recovering deleted files, Metasploit was not affected by attacks on the used versions of Windows and Android, and Autopsy failed to recover deleted files despite being able to identify them.